2008
DOI: 10.1007/s10529-008-9746-x
|View full text |Cite
|
Sign up to set email alerts
|

l-Ribulose production from l-arabinose by an l-arabinose isomerase mutant from Geobacillus thermodenitrificans

Abstract: Geobacillus thermodenitrificans, with a double-site mutation in L-arabinose isomerase, produced 95 g L-ribulose l(-1 ) from 500 g L-arabinose l(-1) under optimum conditions of pH 8, 70 degrees C, and 10 units enzyme ml(-1) with a conversion yield of 19% over 2 h. The half-lives of the mutated enzyme at 70 and 75 degrees C were 35 and 4.5 h, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 13 publications
2
17
1
Order By: Relevance
“…This yield is higher than that (19%) catalyzed by L-AI mutant from G. thermodenitrificans. 24) To our knowledge, this is the first report demonstrating the feasibility of continuous production of L-ribulose with an immobilized enzyme. Immobilization of BLAI on Eupergit C might prove valuable as a cost-effective means of industrial-scale production of L-ribulose.…”
Section: Continuous Production Of L-ribulose From L-arabinose With Immentioning
confidence: 89%
See 1 more Smart Citation
“…This yield is higher than that (19%) catalyzed by L-AI mutant from G. thermodenitrificans. 24) To our knowledge, this is the first report demonstrating the feasibility of continuous production of L-ribulose with an immobilized enzyme. Immobilization of BLAI on Eupergit C might prove valuable as a cost-effective means of industrial-scale production of L-ribulose.…”
Section: Continuous Production Of L-ribulose From L-arabinose With Immentioning
confidence: 89%
“…As listed in Table 4, although the K m of the immobilized BLAI was higher than that of the other L-AIs, its V max value was higher than that of the others. In addition, the immobilized BLAI had the longest t 1=2 , 707, 236, 106, and 6.6 times than that of free enzymes from Bacillus halodurans, 22) Geobacillus stearothermophilus, 22) Thermotoga neapolitana 23) and B. licheniformis, 5) and Geobacillus thermodenitrificans 24) respectively.…”
Section: Characterization Of the Blai Immobilized On Eupergit Cmentioning
confidence: 96%
“…L-Ribose has been produced from L-ribulose using mannose-6-phosphate isomerase (MPI) from Bacillus subtilis with a conversion yield of 70% (17). In this study, the production of L-ribose from L-arabinose was demonstrated via a two-enzyme system from G. thermodenitrificans, in which L-ribulose was first produced from L-arabinose by AI and subsequently converted to L-ribose by MPI.The analysis of monosaccharides and the purification and thermostability of AI and MPI from G. thermodenitrificans (2) isolated from compost were performed as described previously (7,18,19). The cross-linked enzymes were obtained from the treatment of 0.5% glutaraldehyde (10, 16).…”
mentioning
confidence: 99%
“…The analysis of monosaccharides and the purification and thermostability of AI and MPI from G. thermodenitrificans (2) isolated from compost were performed as described previously (7,18,19). The cross-linked enzymes were obtained from the treatment of 0.5% glutaraldehyde (10, 16).…”
mentioning
confidence: 99%
See 1 more Smart Citation